Predicting Psychopathological Onset: Early Signs of Neuropsychiatric Diseases - Costanzi, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this Special Issue is to collect valuable contributions from scientists worldwide working on the role that biological, behavioral, and cognitive markers can have in predicting the onset of neuropsychiatric disorders. We were able to collect 13 original articles and two reviews on this topic. The results published in this Special Issue could provide significant support in pre-clinical phases for the identification of vulnerability factors, to better understand the course of the illness, and to predict its outcome, as well as aiding clinicians in the therapeutic decision-making process.